Evaluation of Bilingual Mathematics Learning Program at Al-Azhar Islamic Middle School, South Tangerang - Dwi Apriliani; Budi Manfaat; Arif Muchyidin (Journal of General Education and Humanities, 2022)
This study evaluates the bilingual mathematics learning program at SMP Islam Al-Azhar 25, South Tangerang. The evaluation model used is CIPP (Context, Input, Process, Product). Data collection techniques using interviews, observation, and document analysis. The evaluation results show that the bilingual mathematics learning program at SMP Islam Al-Azhar 25 South Tangerang has been running well. The program aims to follow the school's "globally competitive" vision. Facilities and infrastructure are categorized as very good, teachers have met the academic qualifications of undergraduate Mathematics Education, students have met the qualifications with tested students through the stages of entering the bilingual class, and the readiness of teachers and students of class VII is categorized as good, and the readiness of teachers and students of class VIII categorized as very good. The mathematics learning process uses the Bilingual Immersion type of learning, with a translation and transcription approach. The average score for daily assignments and tests is above the KKM (Minimum Completeness Criteria). The evaluation component has met the criteria for success, but some need to be improved and developed, such as the availability of a language laboratory and the development of bilingual classes from two classes to all classes so that there are no social gaps.